Burkina Faso - land, climate, energy, agriculture and development: A study in the Sudano-Sahel Initiative for regional development, jobs, and food security - Mouhamadou Bamba Sylla; Kangbéni Dimobe; Safietou Sanfo (University of Bonn, Center for Development Research (ZEF), 2021)
In this working paper, the biophysical factors and socio-economic conditions that led to Land Use and Land Cover Changes (LULC) and land degradation in Burkina Faso are reviewed. It is found that the country is densely populated and population continues to rise at a rate of more than 3% a year. However, nearly half of the population still lives below the poverty line. The electrification relies heavily on fossil fuels as the country has limited hydropower potential and solar energy received little investment. The rate of electrification is still very low, triggering the use of other sources of energy derived from firewood in rural areas. In addition, Burkina Faso has experienced land degradation in the North as a consequence of the 1970s and 1980s droughts that struck all the Sahel. Subsequently, migration took place from the degraded areas to the central, western and southern regions of the country causing further LULC changes. Furthermore, the country suffers from the effects of climate change and climate variability through increasing temperature trends, highly variable precipitation regimes and intensification of extreme events. Projected changes reveal prevailing conditions that indicate an increased risk of disasters in the agriculture, water and health sectors, among others. Due to this situation, some technological responses and policy actions have been developed for sustainable land management and climate change adaptation and mitigation. The adopted technological approaches include, among others, irrigation expansion and efficiency, rainwater harvesting, crop diversification, adoption of drought-tolerant crop varieties and rotational grazing. Some policies have been put in place to facilitate the adoption of these technologies. They consist of carbon trading, land-use zoning and integrated landscape planning, payment for ecosystem services, providing access to markets and agricultural advisory services, securing land tenure and empowering women. These actions are part of broader programs and investment plans that include, but not limited to, the Strategic Framework for Poverty Reduction (SFPR), the Strategy for Accelerated Growth and Sustainable Development (SCADD), the National Rural Sector Program (PNSR), the Resilience and Support Plan for Vulnerable Population (RSPVP) and the Cereals Price Stabilization Program (CPSP) among others.
Keywords: O30; Q24; Q25; Q42; Q54; Q55; Q58; 330; Energy; Land Degradation; Land Management; Technology; Policies; Climate Actions